Book Review: The Interconnected Life of Peter Gerrand - Given, Jock (Journal of Telecommunications and the Digital Economy, 2025)
Peter Gerrand was editor-in-chief of this journal and its predecessors from 1994 to 2015. An engineer trained at Melbourne and Monash universities, he worked from the 1960s to the 1990s at the Melbourne research laboratories of the PMG, Telecom Australia and Telstra. He ran CITRI (1993–1996), the Collaborative IT Research Institute founded by Melbourne and RMIT universities, and Melbourne IT (1996–2000), floating the latter on the Australian Stock Exchange in December 1999. This short autobiography provides astute personal insights into a career that spanned the Australian telecommunications industry’s historic transitions from monopoly to competition, from public to private enterprise, and from analogue to digital communications networks.